Dose-dependent effect of human milk on Bronchopulmonary dysplasia in very low birth weight infants - Yan Xu; Zhangbin Yu; Qianqian Li; Jinjun Zhou; Xiaoguang Yin; Yuelan Ma; Yujie Yin; Shanyu Jiang; Rongping Zhu; Yue Wu; Liangrong Han; Yan Gao; et al. (BMC, 2020)
Abstract Background and aim Human milk has potential protective effects against bronchopulmonary dysplasia (BPD). However, studies on the association between the dose of human milk and BPD in China are limited. This study aimed to evaluate the dose-dependent effects of human milk on BPD and other neonatal morbidities in very low birth weight (VLBW) infants. Methods This retrospective cohort study of preterm infants was conducted on preterm infants of gestational age ≤ 34 weeks and birth weight < 1500 g admitted to the multicenter clinical research database for breastfeeding quality improvement in Jiangsu province. The multivariate analysis was performed to compare the effect outcomes of daily graded doses [1-24 mL/(kg · day), 25-49 mL/(kg · day), and ≥ 50 mL/(kg · day) of body weight] of human milk on neonatal outcomes throughout the first 4 weeks of life versus a reference group receiving no human milk. The models were adjusted for potential confounding variables. Results Of 964 included infants, 279 (28.9%) received exclusive preterm formula, 128 (13.3%) received 1-24 ml/(kg · day), 139 (14.4%) received 25-49 ml/(kg · day), and 418 (43.4%) received ≥50 ml/(kg · day) human milk for the first 4 weeks of life. Compared with infants receiving exclusive formula, those receiving the highest volume of human milk daily [≥50 mL/(kg · day)] had lower incidences of BPD [27.5% in ≥50 mL/(kg · day) vs 40.1% in 0 mL/(kg · day) human milk, P = 0.001)], moderate and severe BPD [8.9% in ≥50 mL/(kg · day) vs 16.1% in 0 mL/(kg · day), P = 0.004], necrotizing enterocolitis [NEC; 3.8% in ≥50 mL/(kg · day) vs 10.8% in 0 mL/(kg · day), P = 0.001], late-onset sepsis [LOS; 9.3% in ≥50 mL/(kg · day) vs 19.7% in 0 mL/(kg · day), P <0.01], and extrauterine growth retardation [EUGR; 38.5% in ≥50 mL/(kg · day) vs 57.6% in 0 mL/(kg · day), P <0.01)]. The logistic regression indicated that those receiving ≥50 ml/kg · day human milk had lower odds of BPD [adjusted odds ratio (AOR) 0.453; 95% confidence interval (CI): 0.309, 0.666], moderate and severe BPD (AOR 0.430; 95% CI: 0.249, 0.742), NEC (AOR 0.314; 95% CI: 0.162, 0. 607), LOS (AOR 0.420; 95% CI: 0.263, 0.673), and EUGR (AOR 0.685; 95% CI: 0.479, 0.979). Conclusions A daily threshold amount of ≥50 ml/(kg · day) human milk in the first 4 weeks of life was associated with lower incidence of BPD as well as NEC, LOS, and EUGR in VLBW infants. Trial registration ClinicalTrials.gov Identifier: NCT03453502 . Registration date: March 5, 2018. This study was retrospectively registered.